2016
DOI: 10.1530/eje-16-0325
|View full text |Cite
|
Sign up to set email alerts
|

Surgical cure rates of sporadic medullary thyroid cancer in the era of calcitonin screening

Abstract: Objective: Time trends of the extent of disease at first diagnosis and biochemical cure remain ill-defined for sporadic medullary thyroid cancer (MTC). This investigation aimed to delineate time trends and biochemical cure rates for sporadic MTC. Design: This was an observational study of consecutive patients operated on for sporadic MTC between 1995 and 2015. Methods: Time trends of clinical and histopathological variables indicative of the extent of disease and biochemical cure were calculated for 600 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 39 publications
(36 reference statements)
4
34
0
5
Order By: Relevance
“…These findings both concur with and diverge from previous studies. Machens and Dralle [34] found a significant reduction in the extent of disease and improved biochemical cure with time, while Randle et al[13] found a significant reduction in tumor diameter and extrathyroidal extension but no reduction in tumor stage over time. In studies by de Groot et al [9] and Modigliani et al[11], extrathyroidal extension and stage were found to be the only prognostic factor for biochemical cure.…”
Section: Discussionmentioning
confidence: 99%
“…These findings both concur with and diverge from previous studies. Machens and Dralle [34] found a significant reduction in the extent of disease and improved biochemical cure with time, while Randle et al[13] found a significant reduction in tumor diameter and extrathyroidal extension but no reduction in tumor stage over time. In studies by de Groot et al [9] and Modigliani et al[11], extrathyroidal extension and stage were found to be the only prognostic factor for biochemical cure.…”
Section: Discussionmentioning
confidence: 99%
“…Further molecular and histopathological investigations are needed to better define the behavior of MTC at the time of its diagnosis. It is well known that MTC can have a variable outcome, with some rapidly aggressive variants and others taking an indolent course, irrespective of tumor stage at diagnosis, and with or without distant metastases [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…During the last years, biochemical cure rates of patients with sporadic MTC improved constantly in the era of calcitonin screening [17]. Therefore, the German Association of Endocrine Surgeons recommends routine calcitonin screening before every thyroid operation to exclude or detect MTC [18,19].…”
Section: Why Is Specialization Mandatory?mentioning
confidence: 99%
“…Other studies defined 60-65 pg/ml as cut-off values of calcitonin to detect MTC [21,22]. Earlier detection of MTC leads to better biochemical cure rates, as shown by Machens and Dralle in 2015 [17]. …”
Section: Why Is Specialization Mandatory?mentioning
confidence: 99%
See 1 more Smart Citation